Needs Analysis of Banyuwangi Local Wisdoms Based Reading Materials for Junior High School - Tri - Mulyati; Zainur Rohman (Journal of English Language Teaching and English Linguistics, 2022)
The purpose of this research is to present the result of needs analysis on Banyuwangi local wisdoms based reading materials for Junior High School. The reading materials are limited on the recount texts. Questionnaires and documentation were used to gain the data from eight year students related to the ideal condition and the real condition of English instruction in SMPN 3 Banyuwangi. The data analysis was conducted by following three steps: data collection, data reduction, data presentation, and conclusion or verification. The result indicated that there was a gap between the ideal condition and the real condition of reading activities. Thus, it can be concluded that it is necessary to develop Banyuwangi local wisdoms based reading materials in SMPN 3 Banyuwangi. The development is based on text-based approach by inserting Banyuwangi culture as the discourse, integrate language components, and use student-centered approach.